Aplicação de software para cálculo da capacidade de carga de fundações profundas - Costa, Eduardo Carvalho da (2015)
The presente work has as objective to optimize the process of calculation of deep foundation load capacity, before the development of a computational tool. It provides an introduction to the types of deep foundations, characteristics, dimensions and load capacity calculation methods proposed by Aoki and Velloso (1975) and Décourt and Lent (1978). The methods of analysis are based on the SPT test (Standard Penetration Test) and made up of coefficients that automatically implemented to calculate, represent the wearer an advantage in preparing the deep foundations of design. The work shows in their results, the tool developed and steps of their use by the user. After developed calculation software, test results presented in report with manual spreadsheets using Excel software to validate the results. Finally, it presents load capacity values from tests performed with different types of piles and soils, makes a comparison between these values and evaluates stake which has better load capacity and which of the methods presented more economical solution.